2021
DOI: 10.1017/s1368980021003335
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of iodine nutritional status during pregnancy by estimated 24-h urinary iodine excretion: population variation range and individual accuracy

Abstract: Objective: To explore the accuracy of estimated 24-hour urinary iodine excretion(24hUIEest) in assessing iodine nutritional status. Design: Fasting venous blood, 24-hour and spot urine samples were collected during the day. The urinary iodine concentration (UIC) and urinary creatinine concentration (UCrC) were measured, and the urinary iodine-to-creatinine ratio (UI/Cr), 24hUIEest, and 24-hour urinary iodine excretion(24hUIE) were calculated. At the population level, correlation and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Finally, median UIC is increased during pregnancy because of a physiological increased renal clearance. Different studies revealed that the median UIC was higher in pregnant women when compared to non-pregnant ones (for instance, 172 µg/L versus 132 µg/L for Stilwell et al) [ 51 , 52 , 53 , 54 ]. Moreover, the percentage of pregnant women with UIC < 50 µg/L is inferior to the percentage of non-pregnant women (7.3% versus 16.8% for Stilwell et al).…”
Section: Physiologic Metabolism During Pregnancymentioning
confidence: 99%
“…Finally, median UIC is increased during pregnancy because of a physiological increased renal clearance. Different studies revealed that the median UIC was higher in pregnant women when compared to non-pregnant ones (for instance, 172 µg/L versus 132 µg/L for Stilwell et al) [ 51 , 52 , 53 , 54 ]. Moreover, the percentage of pregnant women with UIC < 50 µg/L is inferior to the percentage of non-pregnant women (7.3% versus 16.8% for Stilwell et al).…”
Section: Physiologic Metabolism During Pregnancymentioning
confidence: 99%